"Let the little children come": Liturgical Revision and Paedocommunion in the Christian Reformed Church1. (September 2021) - Faber, Ryan L.
This article examines the Lord's Supper liturgies of the Christian Reformed Church in North America (CRC) and inquires into a possible relationship between liturgical changes and the admission of children to the Lord's Supper. The stern warnings and emphasis on communicants' understanding of the sacrament in the CRC's oldest liturgies necessarily excluded children from participating in the sacrament. The 1968 Order for Communion was a milestone in the denomination's liturgical growth. The absence of a preparatory exhortation and lengthy exposition provide a liturgy which can imagine children participating in the Lord's Supper. An increasing emphasis on communicants' communion with one another, evident in the 1981 Service of Word and Sacrament and the formularies adopted by Synods 1994 and 2016 may have helped facilitate the denomination's acceptance of paedocommunion.